2020
DOI: 10.1002/anie.202006398
|View full text |Cite
|
Sign up to set email alerts
|

α‐Functionalisation of Ketones Through Metal‐Free Electrophilic Activation

Abstract: Triflic anhydride mediated activation of acetophenones leads to highly electrophilic intermediates that can undergo a variety of transformations when treated with nucleophiles. This electrophilic ketone activation gives access to α‐arylated and α‐oxyaminated acetophenones under metal‐free conditions in moderate to excellent yields and enables extension to the synthesis of arylated morpholines via generation of vinylsulfonium salts. Computational investigations confirmed the transient existence of intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 81 publications
0
17
0
3
Order By: Relevance
“…Thus far, carbonyl activation has been limited to amides, which implies that enhanced nucleophilicity of the amide carbonyl oxygen is necessary. Recently, Maulide and coworkers demonstrated that the substrate scope could be extended beyond amides and that aryl ketones 55 underwent efficient redox α-arylation to 56, [26] based on the [3,3]-sigmatropic rearrangement of the alkyne-sulfoxides adduct (Scheme 16). [27] The authors proposed that the keteniminium analog I may be in equilibrium with the vinyl triflate II before they are trapped by the sulfoxides.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Thus far, carbonyl activation has been limited to amides, which implies that enhanced nucleophilicity of the amide carbonyl oxygen is necessary. Recently, Maulide and coworkers demonstrated that the substrate scope could be extended beyond amides and that aryl ketones 55 underwent efficient redox α-arylation to 56, [26] based on the [3,3]-sigmatropic rearrangement of the alkyne-sulfoxides adduct (Scheme 16). [27] The authors proposed that the keteniminium analog I may be in equilibrium with the vinyl triflate II before they are trapped by the sulfoxides.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Over the past few decades, significant advances have been achieved in developing novel and efficient methods for the synthesis of α-functionalized ketones because such compounds are versatile intermediates for the construction of a variety of natural products, advanced materials, as well as pharmaceuticals and related compounds. , Recently, the direct C­(sp 3 )-H functionalization reactions have been regarded as a promising approach for the α-functionalization of ketones due to their advantages such as atom- and step-economy. Based on this strategy, various solutions to the formation of α-functionalized ketones have been provided, including the iodine-promoted transformation, transition metal catalysis, and so on. For example, Maulide’s group in 2020 reported a triflic anhydride-mediated α-arylation of acetophenones via metal-free electrophilic activation (Scheme a, top) . Later, Nishikata and co-workers developed an efficient copper-organocatalyst system for the C–H alkylation of ketones (Scheme a, middle) .…”
Section: Introductionmentioning
confidence: 99%
“…The development of novel approaches for the synthesis of α-arylated carbonyl compounds remains a topic of interest in synthetic chemistry. Whereas classical approaches rely on transition-metal-catalyzed couplings of carbonyl-derived enolates with aryl halides or pseudohalides (Scheme A), complementary transition-metal-free methods based on electrophilic aromatic derivatives such as sulfur­(IV), bismuth­(V), iodine­(III), and arynes have emerged in the last years. Alternative methodologies employing N -alkoxyenamines, enolonium equivalents, oxy-allyl cations, and radical-mediated arylations have also been developed.…”
mentioning
confidence: 99%